Tau deletion prevents stress-induced dendritic atrophy in prefrontal cortex: role of synaptic mitochondria - Lopes, Sofia Oliveira (2017)
Tau protein in dendrites and synapses has been recently implicated in synaptic degeneration and neuronal malfunction. Chronic stress, awell-known inducer of neuronal/synaptic atrophy, triggers hyperphosphorylation of Tau protein and cognitive deficits. However, the cause–effect relationship between these events remains to be established. To test the involvement of Tau in stress-induced impairments of cognition,we investigated the impact of stress on cognitive behavior, neuronal structure, and the synaptic proteome in the prefrontal cortex (PFC) of Tau knock-out (Tau-KO) and wild-type (WT) mice. Whereas exposure to chronic stress resulted in atrophy of apical dendrites and spine loss in PFC neurons as well as significant impairments in working memory in WT mice, such changes were absent in Tau-KO animals. Quantitative proteomic analysis of PFC synaptosomal fractions, combined with transmission electron microscopy analysis, suggested a prominent role for mitochondria in the regulation of the effects of stress. Specifically, chronically stressed animals exhibit Tau-dependent alterations in the levels of proteins involved in mitochondrial transport and oxidative phosphorylation aswell as in the synaptic localization of mitochondria in PFC. These findings provide evidence for a causal role of Tau in mediating stress-elicited neuronal atrophy and cognitive impairment and indicate that Tau may exert its effects through synaptic mitochondria.